1986
DOI: 10.1128/jcm.24.3.478-481.1986
|View full text |Cite
|
Sign up to set email alerts
|

Detection of elevated levels of 2-5A synthetase in serum from children with various infectious diseases

Abstract: By a sensitive radioimmunoassay method, (2'-5')oligoadenylate synthetase was detected in serum from patients with viral, bacterial, or mycoplasmal infections at elevated levels compared with enzyme levels in serum from healthy individuals and patients suffering from noninfectious diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…One such intermediate is 2′‐5′ oligoadenylate synthetase (2‐5AS), an intracellular enzyme induced by all three types of IFNs – alfa, beta and gamma. 2‐5AS catalyzes the formation of 2′‐5′ oligoadenylate (2‐5A) from adenosine triphosphate in the presence of double‐stranded RNA 9–14 . 2‐5AS is thought to play an important role in the antiviral action of IFN through its control of the ribonuclease system, which is activated by 2‐5AS.…”
Section: Introductionmentioning
confidence: 99%
“…One such intermediate is 2′‐5′ oligoadenylate synthetase (2‐5AS), an intracellular enzyme induced by all three types of IFNs – alfa, beta and gamma. 2‐5AS catalyzes the formation of 2′‐5′ oligoadenylate (2‐5A) from adenosine triphosphate in the presence of double‐stranded RNA 9–14 . 2‐5AS is thought to play an important role in the antiviral action of IFN through its control of the ribonuclease system, which is activated by 2‐5AS.…”
Section: Introductionmentioning
confidence: 99%
“…2'.5'-Oligoadenylate synthetase (2)(3)(4)(5), an enzyme specifically induced by IFN, is thought to reflect the in t,iL,o state of the IFN system (15-17). 2-5 AS activity in peripheral blood mononuclear cells (PBMC) and serum can be detected even in patients whose serum IFN level is undetectable (12, 14), and its measurement is easy and reproducible (18,19). It has been reported that patients with CHB have normal levels of 2-5 AS activity in PBMC and serum (15,19); however, 2-5 AS activity during acute exacerbation has not been shown.…”
mentioning
confidence: 99%
“…It has been shown that 2',5'-oligo(A) synthetase activity is increased in PBML during virus infection (2,4,7,20,22,37,38) or treatment with IFN (20,23,26) and that the increased activity persists for at least 24 h after administration of IFN (26). Activity of 2',5'-oligo(A) synthetase has therefore been measured to determine whether humans and other animals have been infected with virus or are responding to IFN (4,7,12,23,25,26,37,40,44). Viral diseases in cattle cause major economic losses throughout the world.…”
mentioning
confidence: 99%